Karakter Orang Aceh dalam Hadih Maja Populer di Aceh Utara - Nurul Hafiza; Radhiah Radhiah; Safriandi Safriandi (Universitas Malikussaleh, 2025)
This study examines the character of Acehnese people in popular hadih maja in North Aceh. The purpose of this study is to describe the character of Acehnese people in popular hadih maja in North Aceh. The approach of this research is a qualitative approach. The type of this research is descriptive research. The data of this research is popular hadih maja in North Aceh. The data source of this research is community leaders. The data collection techniques for this research are interview techniques, note-taking techniques, and questionnaires. The results of this study are that in popular hadih maja in North Aceh, several sanguine, choleric, melancholic, and phlegmatic character traits were found. Sanguine character, namely selfish, controlled by others, forgiving, creative, and undisciplined. Choleric character, namely strong-willed, impatient, independent, vengeful, angry, brave, and firm. Melancholic character, namely not confident, loyal, thrifty, neat, and socially concerned Phlegmatic character, namely wise, stubborn, tolerant, patient, avoiding responsibility and loving peace.